Islamic Education Based on the Aswaja Understanding in Character Building the Young Generation in the Digital Era - Idhar, Idhar (Prodi PAI STIT Sunan Giri Bima, 2025)
Islamic education based on the Ahlussunnah Wal Jama'ah paradigm plays a strategic role in shaping the character of the younger generation in the digital age. This study aims to examine the significance of Aswaja-based Islamic education in shaping ethical and resilient character amid rapid technological change. Using a qualitative research design with a library-based approach, data were collected through document analysis and analyzed using content analysis techniques. The findings show that Aswaja-based Islamic education emphasizes the core values of tawassuth (moderation), tawazun (balance), tasamuh (tolerance), and al-'adl (justice), which serve as basic principles in facing digital challenges. These values contribute to the formation of moderate, balanced, tolerant, and just character among the younger generation. In addition, this study reveals that Aswaja functions as a moral and spiritual framework that transforms digital technology from a potential threat into a means of ethical development. The integration of Aswaja values strengthens spiritual resilience and social harmony, enabling young people to face global disruptions without losing their moral compass. This study concludes that Aswaja-based Islamic education offers an adaptive and contextual framework that connects technological advancement with spiritual integrity, serving as a mechanism to prevent radicalism and moral degradation in cyberspace while fostering morally grounded and socially responsible digital citizens.